Hearts in the fire, heads in the fridge: A qualitative investigation into the temporal patterning of the precompetitive psychological response in elite performers - Mellalieu, S. D.; Hanton, S.; Shearer, D. A. (Journal of Sports Sciences, 2008)
Retrospective perceptions and causal beliefs regarding the temporal patterning of precompetitive psychological responses were examined in 12 elite rugby union players. Composite sequence analysis resulted in a series of temporal networks to describe participants' cognitive, affective, and behavioural responses in a time-to-event paradigm. Match-related cognitions remained stable in the lead up to competition, while perceptions of physical symptoms peaked at the onset of performance. Affective responses were associated with feelings of anxiety and tension in the early temporal phases but excitement, confidence, and efficacy in team-mates directly before competition. Behavioural themes described activities associated with technical and physical preparation, familiarization with environmental conditions, and strategies to control activation states early on or directly before competition. The findings highlight the idiosyncratic and dynamic nature of the temporal patterning of precompetitive responses and the influence that perceptions of the team have upon individual preparation for performance. Implications are discussed in the context of the type and timing of intervention for developing individual and team preparatory routines.